Pengaruh Rasio Keuangan Terhadap Perubahan Laba pada Perusahaan Tekstil dan Garmen yang terdaftar di BEI - Fitriasuri, Fitriasuri; Azzahra, Safira (Universitas Nahdlatul Ulama Blitar, 2024)
This research was taken from 2019 to 2022 which aims to examine the effect of financial ratios on changes in profits in textile and garment manufacturing companies listed on the IDX. Several types of ratios are used as dependent variables in the analysis of financial indicators such as Quick Ratio, Debt to Asset Ratio, and Debt to Asset Ratio. Independent variables include Inventory Turnover, Inventory to Sales Ratio, and Net Profit Margin. All businesses in the textile and apparel sector were included in the population of this study. In the study, 15 companies were taken through purposive sampling technique. The results of the analysis in this study also show that the independent variables do affect the dependent variable. The t test shows that Quick Ratio, Inventory to Sales, and Net Profit Margin all have a positive and statistically significant relationship with changes in profit. So, it can be concluded that Quick Ratio, Inventory to Sales and Net Profit Margin have a significant effect on changes in profit in manufacturing companies in the textile and garment industry subsector. These results prove that the inventory turnover ratio and the ratio of debt to assets have little impact on changes in profit.